Revealing electronic nature of broad bound exciton bands in two-dimensional semiconducting WS2 and MoS2 - Shang, Jingzhi (2019)
Owing to unique electronic, excitonic, and valleytronic properties, atomically thin transition metal dichalcogenides are becoming a promising two-dimensional (2D) semiconductor system for diverse electronic and optoelectronic applications. In an ideal 2D semiconductor, efficient carrier transport is very difficult because of lacking free charge carriers. Doping is necessary for electrically driven device applications based on such 2D semiconductors, which requires investigation of electronic structure changes induced by dopants. Therefore probing correlations between localized electronic states and doping is important. Here, we address the electronic nature of broad bound exciton bands and their origins in exfoliated monolayer (1L) WS2 and MoS2 through monitoring low-temperature photoluminescence and manipulating electrostatic doping. The dominant bound excitons in 1L WS2 vary from donor to acceptor bound excitons with the switching from n- to p-type doping. In 1L MoS2, two localized emission bands appear which are assigned to neutral and ionized donor bound excitons, respectively. The deep donor and acceptor states play critical roles in the observed bound exciton bands, indicating the presence of strongly localized excitons in such 2D semiconductors.